(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Radon concentration, exhalation rate, annual effective dose, radium activity, thorium, uranium potassium and radium equivalent have been measured in the present investigation for soil in the area around the old fertilizer factory in southern of Basrah Governorate. The measurements based on CR39 track detector for passive method, RAD7 for active method and NaI(Tl) for gamma concentration measurements. Average values for radon concentration in soil were 112.04±10.76 Bq/m3 using passive technique and 104.56±6.05 Bq/m3 using RAD7. From the result of the passive technique, area and mass exhalation rates and the annual effective dose were calculated. Gamma ray spectroscopy for the soil samples were performed and found that the average concentrations of 226Ra, 232Th and 40K were 50.89 Bq/kg, 21.74 Bq/kg and 640.4 Bq/kg respectively. Gamma ray hazard indices were calculated and found they are within the world average.